Vivid visual mental imagery in the absence of the primary visual cortex - Bridge, H; Harrold, S; Holmes, E; Stokes, M; Kennard, C (2012)
The role of the primary visual cortex in visual mental imagery has provided significant debate in the imagery literature. Functional neuroimaging studies show considerable variation depending on task and technique. Patient studies can be difficult to interpret due to the diverse nature of cortical damage. The type of cortical damage in patient SBR is exceedingly rare as it is restricted to the gray matter of the calcarine sulcus. In this study, we show that in spite of his near-complete cortical blindness, SBR exhibits vivid visual mental imagery both behaviorally and when measured with functional magnetic resonance imaging. The pattern of cortical activation to visual mental imagery in SBR is indistinguishable from individual sighted subjects, in contrast to the visual perceptual responses, which are greatly attenuated. © 2011 The Author(s).